Growth and yield performance of Vigna radiata (L.) R.Wilczek influenced by altitude, nitrogen dose, planting pattern and time of sowing under sole and intercropping with maize - Muhammad Arshad; Sajjad Ahmad; Ghulam Abbas Shah; Rab Nawaz; Shaukat Ali (Biotechnologie, Agronomie, Société et Environnement, 2020)
Description of the subject. Mungbean (Vigna radiata [L]. R.Wilczek) is an important summer leguminous crop. It is widely grown in South Asia to fulfill the human nutritious demand of protein, minerals, vitamins and bioactive constituents. It is well suited to be intercropped with cereals in N limited soil to enhance crop productivity through biological nitrogen fixation.